Dancing necessities: Infrastructures, interventions, and maintenance - Ullerup Schmidt, Cecilie; Bork-Petersen, Franziska; Schnor, Jonas; Vedel, Karen (Peripeti, 2024)
Summary Situating the vocabulary of infrastructure studies within the field of dance, theatre- and performance studies, the article provides a critical analysis of what has happened infrastructurally within the past 10 years in the Danish field of dance and choreography. Four aspects are taken into account: the landscape and economy of venues, the educational changes, an upsurge of self-organised spaces and cooperatives in the field, and finally the field of critique and self-archiving. Through an analysis across frames of production, presentation, and distribution, we suggest tendencies of how dance and choreography is currently moved by its material and immaterial infrastructures. The conclusion stresses how artistic self-organisation of both production platforms, festivals, and separatist collectives can be understood as infrastructural choreographies: artistic and self-maintaining ways of responding to institutional and educational instability, structural precarity, and normative representation in the Danish landscape of dance and choreography. Resumé Ved brug af et vokabular fra infrastrukturstudier i konteksten af dansevidenskab og teater- og performancestudier giver artiklen en kritisk analyse af, hvad der er sket infrastrukturelt i de seneste 10 år i det danske danse- og koreografifelt. Fire aspekter tages i betragtning: et landskab over scener og tilhørende økonomi, forandringer i de nationale uddannelser indenfor dans og koreografi, en fremkomst af selvorganiserede studios og kooperativer, og endelig betingelserne for kritik og arkivering af dans. Ved at analysere på tværs af rammer for produktion, præsentation og distribution, beskriver vi hvordan dans og koreografi i vores historiske samtid formes af feltets materielle og immaterielle infrastrukturer. Konklusionen foreslår, at kunstnerisk selvorganisering af både produktionsplatforme, festivaler og separatistiske kollektiver kan forstås som infrastrukturelle koreografier: kunstneriske og omsorgsdragende måder at reagere på institutionel og uddannelsesmæssig ustabilitet, strukturel prekaritet og normativ repræsentation i det danske felt for dans og koreografi.